Pediatric Integrative Medicine: An Emerging Field of Pediatrics (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Pediatric integrative medicine is a specialty that blends conventional medicine with evidence-based complementary therapies. Research shows that use of integrative medicine is common in children, especially in those living with chronic illness. Knowledge in several important areas of pediatric integrative medicine has expanded exponentially over the last decade. Despite this progress, many pediatricians and practitioners who work with children remain unaware of developments in this field. The goal of this special issue is to: define pediatric integrative medicine in its modern context, provide a history of the field's evolution, highlight areas where research for its use in children is most robust at this time, and identify areas where research is lacking or evolving. Models of the use of integrative medicine in clinical pediatrics will be examined. Bioethics, informed consent, and provider credentialing will be discussed. Some of the most exciting clinical applications of integrative medicine in pediatrics include the use of mind-body medicine therapies such as guided imagery, hypnosis, and biofeedback for the treatment of pain. Mitigation of toxic stress and its health manifestations in children are another area of great potential application of the mind-body therapies. Other areas include integrative approaches to chronic illness, such as cancer, asthma, arthritis, bowel disease, and other chronic conditions where conventional therapies are necessary, yet leave treatment gaps that can be filled with evidence-based integrative therapies targeting lifestyle elements such as nutrition, sleep, physical activity, and social support that are often overlooked in this patient population. Integrative approaches have great potential in preventative heath. Conditions such as obesity and the metabolic syndrome affect a sobering number of children across all age ranges. Few successful treatment models exist for this patient population. Healthy lifestyle measures learned early in life can be a critical factor in providing a foundation for lifelong health for the child and family. Successful models for the use of integrative medicine in these patient populations are needed and will be explored.